2019
DOI: 10.1155/2019/3741294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria and TB Coinfection at a National Tuberculosis Treatment Centre in Uganda

Abstract: The prevalence of malaria and tuberculosis (TB) coinfection is not well established in countries that are highly burdened for both diseases. Malaria could impair TB containment and increase mortality of TB patients. The objective of this study was to determine the prevalence of malaria/TB coinfection among bacteriologically confirmed adult TB patients at a national TB treatment centre in Uganda. Using a cross-sectional study design we enrolled 363 bacteriologically confirmed adult TB patients, and data on demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…We analysed data from a cross‐sectional study that enrolled bacteriologically confirmed TB patients at the National Tuberculosis Treatment Center (NTTC) in Uganda between August 2017 and March 2018 [16]. In this analysis, the inclusion criteria were adults (≥18 years) with bacteriologically confirmed TB who had AEC measurement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analysed data from a cross‐sectional study that enrolled bacteriologically confirmed TB patients at the National Tuberculosis Treatment Center (NTTC) in Uganda between August 2017 and March 2018 [16]. In this analysis, the inclusion criteria were adults (≥18 years) with bacteriologically confirmed TB who had AEC measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Axillary temperature was measured using a digital thermometer (Royal Care® Model: MT 1027, SOJOY ELECTRONICS, China). The Mtb bacillary load was extracted from the laboratory result slip issued by a peripheral TB diagnostic laboratory and standardised as described in the primary study [16]. Full haemogram parameters were determined on peripheral blood using an automated haemoanalyser (Sysmex ® XN series – XN 1000) at MNRH haematology laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed data from a cross-sectional study that enrolled adult bacteriologically confirmed TB patients at the National Tuberculosis Treatment Centre (NTTC) in Uganda between August 2017 and March 2018. 15 Demographic data, clinical symptoms and signs, full hemogram parameters, CD4+ and CD8+ T-lymphocyte counts were extracted from the master dataset. A full description of methods employed in determination of these variables is provided elsewhere.…”
Section: Study Measurementsmentioning
confidence: 99%
“…A full description of methods employed in determination of these variables is provided elsewhere. 15 CD4+ and CD8+ T-lymphocyte counts were determined by flow cytometry using a flow cytometer (BD FACSCalibur™). We defined CD4+ T-lymphocytopenia as a CD4+ count of <418 cells/mm 3 considering a normal range estimate of 418-2105 cells/mm 3 for Ugandans.…”
Section: Study Measurementsmentioning
confidence: 99%